Admission heart rate in relation to presentation and prognosis in patients with acute myocardial infarction: treatment regimens in German chest pain units = Herzfrequenz bei Aufnahme in Beziehung zu klinischer Symptomatik und Prognose von Patienten mit Herzinfarkt : Therapie in deutschen Chest Pain Units - Perne, A.; Hochadel, Matthias; Giannitsis, Evangelos; Senges, Jochen (Herz, 2016)
BackgroundHigher heart rates on admission have been associated with poor outcomes in patients with an acute coronary syndrome in previous cohorts. Whether such a linear relationship still exists in contemporary high-level care is unclear.MethodsProspectively collected data from patients presenting with myocardial infarction (MI) in centers participating in the Chest Pain Unit (CPU) Registry between December 2008 and July 2014 were analyzed. Patients were classified according to their initial heart rate (I: < 50; II: 50-69; III: 70-89; IV: ≥ 90 bpm). A total of 6,168 patients out of 30,339 patients presenting to 38 centers were included in the study.ResultsPatients in group IV had more comorbidities, while patients in group I more often had a history of MI. Patients in the lowest heart rate group presented significantly earlier to the hospital (4 h 31 min vs. 7 h 37 min; p < 0.05) and had the highest rate of interventions. The overall survival after 3 months was significantly worse in group IV after adjusting for baseline variables. In the subgroup analysis, heart rate was a prognostic factor in the non-ST-segment elevation MI group but not in the ST-segment elevation MI group. The correlation between heart rate and major adverse cardiac events followed a J-shaped curve with worst outcomes in the lowest and highest heart rate groups.ConclusionPatients admitted to a dedicated CPU with the diagnosis of MI and a heart rate > 90 bpm experience reduced survival at 3 months despite optimal treatment. Patients with bradycardia also seem to be at increased risk for cardiovascular events despite much earlier presentation and treatment.
Published online: 28 September 2015
Gesehen am 22.10.2019